2017
DOI: 10.1016/j.engstruct.2016.11.062
|View full text |Cite
|
Sign up to set email alerts
|

Innovative composite steel-timber floors with prefabricated modular components

Abstract: 8An innovative steel-timber composite floor for use in multi-storey residential buildings is presented. The research 9 demonstrates the potential of these steel-timber composite systems in terms of bearing capacity, stiffness and method of 10 construction. Such engineered solutions should prove to be sustainable since they combine recyclable materials in the 11 most effective way. The floors consist of prefabricated ultralight modular components, with a Cross-Laminated Timber 12(CLT) slab, joined together and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 22 publications
(21 reference statements)
0
30
0
Order By: Relevance
“…It can also be observed that the experimental flexural stiffness for specimens C-150-A (EIexp = 2823 kN.m 2 ± 4.2%) almost coincides with the analytical flexural stiffness obtained assuming full composite action, indicating that the specimen is nearly fully composite and that a high shear transfer occurs using such connection detail. Table 3 presents predictions of the flexural stiffness of the tested floors derived using existing models in [1], [6] and [9] as well as their deviation from experimental data. For each connection type, the analytical flexural stiffness was determined using results from the average pushout tests (in particular, k0.75).…”
Section: Analytical Predictions 41 Full-composite Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can also be observed that the experimental flexural stiffness for specimens C-150-A (EIexp = 2823 kN.m 2 ± 4.2%) almost coincides with the analytical flexural stiffness obtained assuming full composite action, indicating that the specimen is nearly fully composite and that a high shear transfer occurs using such connection detail. Table 3 presents predictions of the flexural stiffness of the tested floors derived using existing models in [1], [6] and [9] as well as their deviation from experimental data. For each connection type, the analytical flexural stiffness was determined using results from the average pushout tests (in particular, k0.75).…”
Section: Analytical Predictions 41 Full-composite Actionmentioning
confidence: 99%
“…Cold-formed steel (CFS) and timber-based flooring systems have become increasingly popular in the construction industry due to their attractive high strength-to-weight ratio, buildability and sustainability [1,2]. While, the composite design of such floors provides an attractive solution for increasing the efficiency of lightweight floors and minimising the use of resources, the beneficial effect of the timber board (often referred to as floor boards or decking) on the floor structural performance is often ignored, leading to a more conservative design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These systems have been developed in Italy [3,[5][6][7][8], in Canada [4,[9][10][11][12][13], in the UK [1,14] and in Austria [15]. Similar systems as in [4] have been developed in Australia but using LVL (Laminated Veneer Lumber) instead of CLT (Cross Laminated Timber) [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The structural performance of timber-to-steel composite joints and beams has been comprehensively studied by Hassanieh et al [3]- [5] and Loss and Davison [6] and Loss et al [7], but research on timber-to-timber connections mainly focuses on the behaviour, analysis and modelling of dowel type connectors and the structural performance of lap and/or edge joints [8], [9], with less attention being paid to the structural behaviour of timber-totimber composite connections [10], [11]; in particular to CLT-LVL and CLT-Glulam composite connections for the development of prefabricated timber-timber composite (TTC) floors. Recently, Branco et al [12] investigated the in-plane behaviour of traditional timber floors strengthened with CLT panels using SFS, HBS and VGZ screws installed normal and inclined (at 45°) to the shear plane.…”
Section: Introductionmentioning
confidence: 99%